Recepcija in udejanjenje liturgične prenove drugega vatikanskega cerkvenega zbora v Cerkvi na Slovenskem - Krajnc, Slavko (Bogoslovni vestnik, 2024)
This paper seeks to show how the liturgical renewal of the Second Vatican Council was the result of several decades of liturgical movement or rather of “incentives from below”, which found in the eyes of the Popes, especially Pius X. and Pius XII., recognition and approval. These incentives have become a sign and witness of the indestructible youth of the Church and the basis of the Constitution on the Sacred Liturgy. The general acceptance of the renewed liturgy in Slovenia encouraged first the priests to the study of liturgy (“ritus et preces”, SC 48), and then the faithful to a deeper understanding, fruitful cooperation and greater enthusiasm for the life from the secret of liturgy. In the realization of renewal steps of the liturgy, which was based on loyalty to the tradition (hence slow update steps) and entitled openness for development (“aggiornamento”), as well asissuing instructions, manuals and liturgical books, the Slovenian Church did not lag behind others, but rather in its enthusiasm it followed other nations and, some individuals, here and there imitated even progressive deviations of the permitted. Believers have owing to Slovenian priests, who were inflamed and imbued with spiritual enthusiasm, to whom liturgy has become “the fulfilment of their priestly office” (PO 2,4), accepted liturgy as a school, as well as the “source and summit of Christian life” (SC 10).
Keywords: drugi vatikanski cerkveni zbor; liturgical books; liturgical movement; liturgične knjige; liturgično gibanje; prenova bogoslužja v Sloveniji; renewed liturgy in Slovenia; the Second Vatican Council